MYTHS AND FACTS OF BIOSIMILAR MONOCLONAL ANTIBODIES - João Gonçalves (Revista Portuguesa de Farmacoterapia, 2015)
With this article we intend to present facts and to expose several myths concerning the quality, safety and efficacy of therapeutic biosimilar monoclonal antibodies. We wish to summarize the experience of EMA regarding the biosimilar mAb and address the outstanding issues concerning the regulation and continuous supervision of these products. These issues include the conditions necessary to extrapolate the indications of the biosimilars of monoclonal antibodies for uses other than the ones initially evaluated in clinical comparability. Moreover, the issues related to the impact of changes in the manufacturing of biosimilars, or of biological reference medicines, continue to be a major point of discussion. Since the quality of biotech medicines is crucial for the efficacy and safety of monoclonal antibodies, an effective approach of the variables involved in this process is important for an independent evaluation of these products. The scientific basis for the discussion of the quality, efficacy and safety of the biosimilar medicines will not only overcome the myths that label these products, but also raise regulatory requirements for the approval of biotech medicines, guaranteeing that their use by patients and healthcare professionals is safe.